Induced plant responses of different Lantana camara L. (Verbenaceae) varieties to herbivory by Falconia intermedia (distant) (Hemiptera: Miridae) - Heshula, Unathi-Nkosi Lelethu Peter (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2010)
A highly variable invasive shrub, Lantana camara L. (Verbenaceae), has been notoriously difficult to control thus far despite a well established biological control programme in South Africa. A promising leaf-feeding biological control agent, Falconia intermedia (Distant) (Hemiptera: Miridae), released to control this invasive plant eventually crashed at three out of five sites in the Eastern Cape Province. In the Mpumalanga Province, after initially colonising and building up high numbers on the L. camara stands the agent populations crashed. Several reasons for these population crashes have been suggested, but induced plant defences have not been investigated. Although plants face the challenge of herbivory by various organisms while remaining immobile, some plants may possess the ability to induce physical and/or chemical defensive responses following feeding and thus prevent further plant tissue damage and loss. Laboratory trials were conducted to determine the existence, nature and effect of physical and chemical feeding-induced responses of L. camara on the performance of the leaf-feeding biological control agent, F. intermedia. Lantana camara plants used in the study were obtained from five localities in the Eastern Cape Province, South Africa, while the insect culture was established from field populations. Plants from all varieties on which F. intermedia was released significantly increased the toughness of their leaves compared to control treatment plants. In addition, plants from three localities: Lyndhurst Farm, East London and Port Alfred, significantly increased trichome density after prolonged feeding by F. intermedia. On the three varieties showing increases in these two factors (i.e. leaf toughness and trichome density), oviposition, survival and feeding damage by the mirid agent was significantly lower on previously damaged plants. A significant negative correlation between trichome density and population numbers was found (RÂ²= 0.52, p < 0.0003), suggesting that an increase in trichome density strongly contributes to a reduction in F. intermedia's growth. The growth and reproduction of the resistant plants was not significantly impacted by F. intermedia feeding. The defensive responses were found to be plant systemic and rapidly induced as they were elicited and expressed throughout the plant in both damaged and undamaged leaves within five weeks after insect release. Leaf toughness and trichome density were not significantly increased after feeding on plants from Whitney Farm and Heather Glen Farm. On the contrary, mirid individuals performed significantly better on plants from Whitney Farm and Heather Glen Farm than on plants of other varieties, indicating their susceptibility and suitability to the agent and the lack of induced resistance against the agent. Plants from all localities besides East London showed some level of tolerance and overcompensated for feeding damage by increasing plant growth and reproductive factors on plants fed upon. This was however only significant in two variables of the more susceptible localities, Whitney Farm and Heather Glen Farm. This increase in plant fitness did however indicate an induced defence response by these plants to feeding, a response designed to lessen the effects of agent feeding. Headspace volatile analysis was used to investigate any volatile chemical responses by L. camara due to F. intermedia feeding at two of the five localities chosen: East London and Whitney Farm. There was no significant difference in headspace volatiles emitted by leaves of plants from the East London insect infested and control treatment plants. On the Whitney Farm damaged plants however there was a 2.5 fold increase in the emission intensity of one of the three main compounds, later identified as Beta-caryophyllene. Three major chemical constituents which were found to be common to leaf volatiles of the two varieties were identified through gas chromatography-mass spectrometry (GC-MS) from the damaged and undamaged leaves of these two varieties. The methods used in collecting leaf volatiles were shown to be significant in the strength of chromatogram peaks. Using general authentication methods and purified standards, one of these was identified as the sesquiterpene, Beta-caryophyllene (Câ‚ â‚…Hâ‚‚â‚„). This compound is one of the major constituents found in isolations of L. camara varieties worldwide. This is the first such work done on a variety of L. camara in South Africa, and hopefully the beginning of more in-depth studies of the volatile organic chemicals from the numerous naturalised varieties of L. camara. It is suggested that the sum of these responses may play a role bigger than is currently understood in this plant-insect relationship. It is also argued that feeding induced plant defences may play an important role in attempts to control alien plants using insect agents.
Keywords: Lantana camara -- South Africa -- Eastern Cape; Lantana camara -- Biological control -- South Africa -- Eastern Cape; Biological pest control agents -- South Africa -- Eastern Cape; Weeds -- Biological control -- South Africa -- Eastern Cape; Invasive plants -- Biological control -- South Africa -- Eastern Cape; Hemiptera -- South Africa -- Eastern Cape; Miridae -- South Africa -- Eastern Cape